Effect of 7-Hydroxy-2-(4- Hydroxy -3-Methoxyphenyl)-Chroman-4-one On Level of Mangan-Superoxide Dismutase (Mn-Sod) and Superoxide Dismutase 2 (Sod2) Gene Expression in Hyperlipidemia Rats - Rahmah Dara Ayunda; Prasetyastuti Prasetyastuti; Pramudji Hastuti (Indonesian Journal of Pharmacy, 2019)
Hyperlipidemia is a lipid metabolism disorder characterized by an increase in serum lipid levels. Hyperlipidemia is a major risk factor for many metabolic syndrome diseases because it triggers oxidative stress. Oxidative stress can be reduced by endogenous antioxidant enzymes triggered by exogenous antioxidant compounds, such as 7-OH-2- (4-OH-3-methoxyphenyl)-chroman-4-one isolated from the seeds of Swietenia macrophylla King. The aims of this study were to investigate the effects of 7-OH-2-(4-OH-3-methoxyphenyl)-chroman-4-one compounds on cholesterol level, LDL level, Mn-SOD levels and SOD2 gene expression of hyperlipidemic rats. Thirty rats (Rattus norvegicus ) were divided into 6 groups, normal group (N), hyperlipidemia group (HL), hyperlipidemia group with simvastatin (P), hyperlipidemic group with 7-OH-2-(4-OH-3-methoxyphenyl)-chroman-4-one with dose 10 (F10), 30 (F30) and 90 (F90) mg/200g body weight (BW). Cholesterol and LDL were analyzed with CHOD-PAP method, Mn-SOD level was analyzed by ELISA method and SOD2 gene expression was analyzed by qPCR method. The decrease in cholesterol and LDL levels were most prevalent in group F90 with dose 90 mg/200g BW of 7-OH-2-(4-OH-3-methoxyphenyl)-chroman-4-one, with average difference each of them was 172.43 mg/dL and 36.12 mg/dL. The rats fed on high-cholesterol diet exhibited a significant elevation in Mn-SOD levels (p<0.05) compared to normal group. The treated animals with 7-OH-2-(4-OH-3-methoxyphenyl)-chroman-4-one has the level of Mn-SOD is significantly lower (p<0.05) compared with hyperlipidemic group. Expression of SOD2 in group F90 has value close to normal group (p> 0.05). 7-OH-2-(4-OH-3-methoxyphenyl)-chroman-4-one with dose of 90 mg/200g BW improved cholesterol levels, LDL levels, Mn-SOD levels and SOD2 gene expression in hyperlipidemic rats.